Linguocultural characteristics of phraseological units with the component “wind” in English and Uzbek languages - Rakhmatullaeva, Shakhnoza Abdurazoq qizi (The Lingua Spectrum, 2026)
This article investigates the linguocultural characteristics of phraseological units containing the component “wind” in English and Uzbek. Phraseological expressions often reflect the cultural worldview, historical experience, and symbolic thinking of a nation. The study aims to analyze the semantic, metaphorical, and cultural meanings embedded in wind-related phraseological units in the two languages and to identify their similarities and differences. The research applies comparative and descriptive methods to examine selected phraseological units from English and Uzbek linguistic sources and dictionaries. The analysis shows that in both languages the concept of wind is frequently associated with ideas such as speed, change, instability, and disappearance. However, cultural and linguistic differences influence how these meanings are expressed in phraseological structures. In English, wind often symbolizes change or hidden information, while in Uzbek it commonly represents transience, rapid movement, or wastefulness. The results demonstrate that phraseological units with the component “wind” serve as important carriers of cultural knowledge and reflect the unique linguistic worldview of each nation.